"I'm struggling but I'm not suffering" The lived experience of persons with young onset dementia in Ireland: An Interpretative Phenomenological Analysis - Moore, Vanessa (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2021)
Abstract: I m struggling but I m not suffering The lived experience of persons with young onset dementia in Ireland: An Interpretative Phenomenological Analysis This PhD thesis is an exploration of the lived experiences of persons with young onset dementia (YOD) in Ireland. YOD is the term used for dementia in persons under 65 years of age. This population generally have different experiences and needs compared to older persons with dementia; they are often still in employment, have financial responsibilities such as mortgages, have young and dependent children, and have more energy and are physically stronger than older people with dementia. In Ireland, only a handful of studies have been carried out in relation to persons with YOD; it was therefore my aim to explore, and hear in their own voice, the lived experience of persons with YOD in Ireland. The methodology chosen for the thesis was Interpretative Phenomenological Analysis this qualitative approach allowed for in-depth emphasis on the individual experience, focus on the particular, and a double-hermeneutic where to make sense of the part, you look at the whole, and to make sense of the whole, you look at the part. With the help of gatekeepers and using purposive sampling, I found ten persons with YOD willing to participate in the study. I carried out in-depth, semi-structured qualitative interviews with the participants to collect data. These interviews were coded, themes developed, and over-arching themes were developed into Findings chapters. The thesis has three Findings chapters: pathway to diagnosis and disclosure of YOD, experiences of living with YOD, and the personal sphere and YOD. These three chapters detail the lived experience of YOD in Ireland, starting with the unclear, confusing, and slow pathway to care, and poor disclosure process experienced by a number of participants. The second Findings chapter focuses on lived experiences such as the lack of services experienced by the participants, and the pervasive and all-encompassing stigma which made itself known in both personal and systemic experiences. The third Findings chapter outlines the experiences of the participants in relation to difficulties with and ceasing employment, worries and concerns for children, and the ability to live well despite the challenges dementia brings. This PhD thesis explored the lived experiences of people with YOD in Ireland, and found that pathways to care and interactions with health care professionals were both in need of improvement. More and better supports and services, chronically underfunded and ignored despite over 20 years of highlighting of the issue, are urgently needed. Finally, and equally important, the stigma around YOD must be challenged, to show that while living with YOD may be a struggle, it does not have to mean suffering, and that living well with the illness is possible.
APPROVED
Keywords: Interpretative Phenomenological Analysis; dementia; Alzheimer's Disease; Ireland; young onset dementia